Is sedentary behaviour just physical inactivity by another name? - Hidde P. van der Ploeg; Melvyn Hillsdon (BMC, 2017)
Abstract The relationship between sedentary behaviour and physical activity and their role in the development of health conditions is an ongoing topic of research. This debate paper presents arguments in favour and against the statement: "Is sedentary behaviour just physical inactivity by another name?" The paper finishes with recommendations for future research in the field of sedentary behaviour, physical activity and public health.